The Association between Short or Long Sleep Times and Quality of Life (QOL): Results of the Korea National Health and Nutrition Examination Survey (KNHANES IV–V) - Jae‐Hyun Kim; Eun‐Cheol Park; Ki‐Bong Yoo; Sohee Park (2015)
Sleep can affect quality of life (QOL). We examined the association between self-reported sleep time and QOL independent of perceived health status and depressive disorder using the EuroQol-5 Dimension (EQ-5D) and a visual analog scale (VAS).We used the nationwide cross-sectional survey data of 28,178 subjects from the Korea National Health and Nutrition Examination Survey (KNHANES) IV-V. Self-reported sleep time was assessed by average hours of sleep per day. QOL was measured using the EQ-5D and VAS. A generalized additive model and multiple linear regression analysis were used to estimate the effect of sleep time on the QOL while adjusting for potential confounding variables.We found a significant inverted U-shaped relationship between sleep time and QOL using both the EQ-5D and VAS indices. Compared with subjects who slept 7 h/day, Korean men whose sleep time was very short (≤ 4 h/ day) or very long (≥ 10 h/day) had substantially worse QOL (-3.125 in EQ-5D, p < 0.001 and -4.387 on the VAS, p = 0.000 for ≤ 4 h/day; -1.763 in EQ-5D, p = 0.001 and -1.944 on the VAS for ≥ 10 h/day, all p = 0.038). A similar inverted U-shape was observed between sleep time and QOL in Korean women.Inappropriate sleep time (either short or long) in both men and women was significantly associated with lower QOL. In particular, such an association was more apparent among persons whose perceived health status was poor.